IMPROVING STUDENTS’ READING COMPREHENSION THROUGH THE USE OF RECIPROCAL TEACHING TECHNIQUE AT STMIK RIAU PEKANBARU - LIYA ASTARILLA; DEDE WARMAN (English Study Program University of Pasir Pengaraian, 2016)
This research aimed to describe and explain to what extent Reciprocal Teaching could improve the reading comprehension of semester II/E students of STMIK Riau Pekanbaru and the factors that influenced the change of their reading comprehension through Reciprocal Teaching. This research was a classroom action research, every cycle consisted of four four fundamental aspects namely, planning , action, observation, and reflection. The participants of this research were the semester II/E students majoring in Computer Science/Informatics STMIK Riau Pekanbaru totalling 35 students. The instruments of this research were a reading comprehension test, an observation sheet, field note, and interview. There were two main findings of this research: (1) Reciprocal Teaching could improve thestudents’ reading comprehension; (2) Teaching material, class acitivity, class management, and lecturer’s approach were the factors that could influence the change of students’ reading comprehension.